The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0100-736x2004000400010
|View full text |Cite
|
Sign up to set email alerts
|

O surto de peste suína africana ocorrido em 1978 no município de Paracambi, Rio de Janeiro

Abstract: Em função das dúvidas que ainda perduram 25 anos após a ocorrência do surto de peste suína africana (PSA), em Paracambi, Estado do Rio de Janeiro, Brasil, em 1978, são apresentados os resultados, relativos a este foco, obtidos pelos estudos epidemiológico, clínico-patológico, virológico, bacteriológico e ultra-estrutural dos casos naturais, bem como os relativos à reprodução experimental da doença no Brasil e sua confirmação por isolamento e determinação de patogenicidade realizada no Plum Island Animal Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 2 publications
(6 reference statements)
0
10
0
11
Order By: Relevance
“…Esse reconhecimento englobou grande parte do território nacional e implica no atendimento de requisitos sanitários a serem cumpridos pelos estados. Já a peste suína africana (PSA) foi registrada no País na década de 1980, mas foi erradicada por abate sanitário, e, desde então, não houve mais relatos da doença (Tokarnia et al, 2004;Lyra, 2006).…”
Section: Doenças Da Lista Da Oie Que Afetam Os Suínosunclassified
“…Esse reconhecimento englobou grande parte do território nacional e implica no atendimento de requisitos sanitários a serem cumpridos pelos estados. Já a peste suína africana (PSA) foi registrada no País na década de 1980, mas foi erradicada por abate sanitário, e, desde então, não houve mais relatos da doença (Tokarnia et al, 2004;Lyra, 2006).…”
Section: Doenças Da Lista Da Oie Que Afetam Os Suínosunclassified
“…Sun drying can eliminate almost 90% of the initial HCN content (RAVINDRAN et al, 1987;RAVINDRAN, 1993;WANAPAT et al, 1997). Animals that continuously consume cassava show increased serum levels of the enzyme rhodanase, which is responsible for the detoxification of cyanide, conferring tolerance to HCN levels that would otherwise be toxic (TOKARNIA et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that pods cause hepatocellular necrosis but have not proved that they cause abortions (Tokarnia et al 2000). Apart from the types of lesion arising from photodermatitis and abortions, it has been reported that natural poisoning by the plant has resulted in animals displaying symptoms of anorexia and depression.…”
Section: β-D-glucopyranosyl-(13)-[α-larabinofuranosyl-(14)]-α-l-rhamentioning
confidence: 99%
“…Morong, a member of the tree family Fabaceae, sub-family Mimosoideae, commonly known in English as the earpod tree and in Portuguese as tamboril and timbauva, is widely distributed throughout Brazil, and is found in all of its geographic regions (Lorenzi 1992;Carvalho 1994;Tokarnia et al 2000).…”
mentioning
confidence: 99%